PENGARUH PEMBERIAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) PADA PERTUMBUHAN BIBIT STEK STEVIA (Stevia rebaudiana Bertoni) - Gabai, Maria; Sumayku, Bertje R.A.; Tulungen, Antje Grace; Tilaar, Wenny; Rogi, Johannes E. X.; Walingkas, Stanley A.F. (EUGENIA, 2024)
Sweetleaf stevia (Stevia rebaudiana Bertoni) is one of the potential sugar-producing plants besides sugar cane which is widely used as a natural non-calorie sweetener. Propagation of stevia by shoot cuttings produces more uniform seedlings. Plant Growth Promoting Rhizobacteria (PGPR) contains a group of beneficial bacteria that live in the plant root ecosystem that can stimulate plant growth. This study aims to determine the effect of PGPR on the growth of stevia cuttings and the best concentration of PGPR on the growth of stevia cuttings. This study was conducted in February-May 2024 in Kolongan Atas II Village, Sonder District, Minahasa Regency, North Sulawesi Province. The study used a Completely Randomized Design (RAL), with 5 treatment levels, namely P0 = Control (Without PGPR), P1 = PGPR 10 ml/liter of water, P2 = PGPR 20 ml/liter of water, P3 = PGPR 30 ml/liter of water and P4 = PGPR 40 ml/liter of water. Each treatment was repeated 4 times.The results showed that the aplication of PGPR affected the growth of stevia cuttings. The best PGPR concentration for the growth of stevia cuttings was at a PGPR treatment concentration of 20 ml/liter of water.  Keywords: plant growth promoting rhizobacteria, stevia